"Proceedings of the International Conference, 2005 on Emerging Securities Market: Challenges and Prospects, Vol.IV: Market Analytics_Researchers Persp" - Rao (Panduranga V) Ed.; Sahoo (M S) Ed.; Rao (Narayana K V S S) Ed.; Rath (Prabhas K) Ed. ("52, Nagarjuna Hills,Hyderabad - 500 082", 2006)
Proceedings ; International Conference
50
Keywords: Proceedings ; International Conference